morph! AN INTERACTIVE APPROACH TO TRANSFORM BUILDINGS TO LIFE - Kozuhovskij, Sergej; Szmidt, Peter; Hemken, Benjamin; Paul, Jennifer; Karayel, Meltem; Riemann, Sonja; Jacob, Martin; Cohrs, Christian; Molnar, Alexander; Trees, Joshua; Schönke, Luisa; Davydenkova, Darya; et al. (International Journal of Computing, 2010)
The use of digital media for interactive art installations is increasingly popular. Art and technology merge. Our intention is to create interactive art installations that offer an incentive to interact playfully with the surrounding environment. Motivated by this, we developed and realised two forms of installations: an interactive screen with several and a light cone installation.